Homeostatic Control of the Crypt-Villus Axis by the Bacterial Enterotoxin Receptor Guanylyl Cyclase C Restricts the Proliferating Compartment in Intestine - Li, Peng (American Society for Investigative Pathology, 2007)
Guanylyl cyclase C (GC-C), the receptor for diarrheagenic enterotoxins and the paracrine ligands guanylin and uroguanylin, regulates intestinal secretion. Beyond volume homeostasis, its importance in modulating cancer cell proliferation and its uniform dysregulation early in colon carcinogenesis, reflecting loss of ligand expression, suggests a role for GC-C in organizing the crypt-villus axis. Here, eliminating GC-C expression in mice increased crypt length along a decreasing rostral-caudal gradient by disrupting component homeostatic processes. Crypt expansion reflected hyperplasia of the proliferating compartment with reciprocal increases in rapidly cycling progenitor cells and reductions in differentiated cells of the secretory lineage, including Paneth and goblet cells, but not enteroendocrine cells. GC-C signaling regulated proliferation by restricting the cell cycle at the G(1)/S transition. Moreover, crypt expansion in GC-C(−/−) mice was associated with adaptive increases in cell migration and apoptosis. Reciprocal alterations in proliferation and differentiation resulting in expansion associated with adaptive responses in migration and apoptosis suggest that GC-C coordinates component processes maintaining homeostasis of the crypt progenitor compartment. In the context of uniform loss of GC-C signaling during tumorigenesis, dysregulation of those homeostatic processes may contribute to mechanisms underlying colon cancer.